Efeito alelopático de Solanum Pimpinellifolium (solanacea) sobre germinação e crescimento inicial de Lactuca Sativa L. e Bidens Pilosa L. - Fioresi, Raiane de Souza (2017)
Allelopathy is any kind of interference caused by chemicals produced by plants in community organisms, resulting in both beneficial and harmful effects. Considering that several species of the genus Solanum present great allelopathic potential, the objective of the present work was to evaluate the allelopathic effect of hexanic, methanolic and leaf acetate extract of Solanum pimpinellifolium on the germination of seeds of cultivated Lactuca sativa L. and wild Bidens pilosa, as a possible alternative to the use of highly polluting and persistent synthetic herbicides in the environment. The extracts were obtained by maceration at room temperature for 7 days. They were then dried and diluted in water at 1, 2 and 5mg / ml concentrations. Then 100 seeds of each species were distributed in 5 petri dishes lined with two sheets of germitest paper moistened with the different concentrations of each extract were put to germinate. The tests were conducted at a constant temperature of 22ºC and constant light in a BOD type germination chamber. The number of germinated seeds was counted daily, obtaining at the end of 7 days, the percentage of germination and germination rate index (IVG). Among the three extracts, the acetate presented a better performance, reducing the speed and the germination percentage for all the concentrations, and that 5mg / ml presented only 8% of germination for L. sativa L. The hexane extract showed better performance, decreasing the velocity and percentage of germination at all concentrations for B. pilosa. The phytochemical analyzes were performed using thin layer chromatography (CCD) technique and identified the chemical groups present in the three extracts used in the experiments. The statistic revealed significant differences between the different treatments and plants tested according to the Scott-Knott test at the 5% probability level.